Nursing Observation of Improved Administration Route of Protamine Sulfate Neutralizing Heparin. (8th March 2022) - Hu, Jia; Zeng, Suiting; Wang, Ziqi; Chen, Qiuping; Shi, Ya; Wu, Yuanzhou
Abstract : In this study, we have evaluated and examined various nursing effects of improved administration of protamine sulfate neutralizing heparin after cardiopulmonary bypass. For this purpose, retrospective analysis was made about the nursing records and clinical data of 216 patients who underwent cardiac operation under cardiopulmonary bypass in our hospital from January 2018 to December 2020. Among the enrolled patients, 118 patients were given subinterval administration of protamine sulfate neutralizing heparin via aortic root with the assistance of the scrub nurse at the end of cardiac surgery (improved group). A total of 98 patients were administered by the circulating nurse via the central vein (regular group). The changes of body temperature, blood pressure, oxygen saturation before and after heparin neutralization, and the total volume of thoracic drainage within 24 hours after operation were observed in the two groups, so as to evaluate the application effect of the improved administration of protamine sulfate neutralizing heparin from the perspective of nursing. There was no significant difference in age, gender, and other basic characteristics between the two groups (P > 0.05 ). The volume of drainage in the improved group and the regular group within 24 hours after surgery was 234 ± 26.3 ml and 307 ± 31.8 ml, respectively, P < 0.01, and the difference was statistically significant. The incidence of adverse reactions in the improved group was much lower than that in the regular group, P < 0.01 . The administration route of the improved group was beneficial to maintain the stability of hemodynamics when using the protamine sulfate to neutralize heparin, which is worthy of clinical nursing promotion.